Long-Lasting Effects of GABA Infusion Into the Cerebral Cortex of the Rat - Teresa Montiel; Daniel Almeida; Iván Arango; Eduardo Calixto; César Casasola; Simón Brailowsky (Neural Plasticity, 2000)
In electrophysiological terms, experimental models of durable information storage in the brain include long-term potentiation (LTP), long-term depression, and kindling. Protein synthesis correlates with these enduring processes. We propose a fourth example of long-lasting information storage in the brain, which we call the GABA-withdrawal syndrome (GWS). In rats, withdrawal of a chronic intracortical infusion of GABA, a ubiquitous inhibitory neurotransmitter, induced epileptogenesis at the infusion site. This overt GWS lasted for days. Anisomycin, a protein synthesis inhibitor, prevented the appearance of GWS in vivo. Hippocampal and neocortical slices showed a similar post-GABA hyperexcitability in vitro and an enhanced susceptibility to LTP induction. One to four months after the epileptic behavior disappeared, systemic administration of a subconvulsant dose of pentylenetetrazol produced the reappearance of paroxysmal activity. The long-lasting effects of tonic GABAA receptor stimulation may be involved in long-term information storage processes at the cortical level, whereas the cessation of GABAA receptor stimulation may be involved in chronic pathological conditions, such as epilepsy. Furthermore, we propose that GWS may represent a common key factor in the addiction to GABAergic agents (for example, barbiturates, benzodiazepines, and ethanol). GWS represents a novel form of neurono-glial plasticity. The mechanisms of this phenomenon remain to be understood.